Die predikant: dienaar van God of net 'n gewone werknemer? - J. V. du Plessis; H. J. Deacon (Acta Theologica)
This article examines the nature of the relationship between the minister and his/her congregation in the Dutch Reformed Church in South Africa. Is the minister in the service of God, or is he/she in the service of the General Synod of the Dutch Reformed Church, the Synod of the relevant province concerned, or the Presbytery within which the congregation falls, or is he/she merely an employee of his congregation? The church ordinance is examined against the background of three relatively recent directional judgements of the courts, and a comparison is drawn between the Dutch Reformed Church and the Anglican Church. It is concluded that the minister is not only a servant of God, but also an employee in the service of the congregation.